Working memory : the connected intelligence - Alloway, Tracy Packiam; Alloway, Ross. (New York : Psychology Press, 2013)
'Working memory--the conscious processing of information--is increasingly recognized as one of the most important aspects of intelligence. This fundamental cognitive skill is deeply connected to a great variety of human experience--from our childhood, to our old age, from our evolutionary past, to our digital future. In this volume, leading psychologists review the latest research on working memory and consider what role it plays in development and over the lifespan. It is revealed how a strong working memory is connected with success (academically and acquiring expertise) and a poor working memory is connected with failure (addictive behavior and poor decision-making). The contributions also show how working memory played a role in our cognitive evolution and how the everyday things we do, such as what we eat and how much we sleep, can have an impact on how well working memory functions. Finally, evidence on the benefits of working memory training is explored.'--P. [4] of cover.
Includes bibliographical references and index.
Keywords: Short-term memory; Memory